Radio Mean Labeling of Some Splitting Graphs. Issue 1 (June 2021) - Palani, K.; Sabarina Subi, S.S.; Maheswari, V.
Abstract: Let G = (V, E) be a simple graph with p vertices and q edges. For a connected graph G of diameter d, a radio mean labeling is a one to one mapping f from V(G) to N satisfying the condition d ( u v ) + [ f ( u ) + f ( v ) 2 ] ≥ 1 + d i a m ( G ) for every μ, ν ∈ V ( G ). The span of a labeling f is the maximum integer that f maps to a vertex of G. The radio mean number of G, r m n ( G ) is the lowest span taken over all radio mean labelings of the graph G. In this paper, we analyze some splitting graphs for radio mean labeling.